Prostate-specific antigen and hormone receptor expression in male and female breast carcinoma - Cohen Cynthia; Kraus Teresa S; Siddiqui Momin T (BMC, 2010)
Abstract Background Prostate carcinoma is among the most common solid tumors to secondarily involve the male breast. Prostate specific antigen (PSA) and prostate-specific acid phosphatase (PSAP) are expressed in benign and malignant prostatic tissue, and immunohistochemical staining for these markers is often used to confirm the prostatic origin of metastatic carcinoma. PSA expression has been reported in male and female breast carcinoma and in gynecomastia, raising concerns about the utility of PSA for differentiating prostate carcinoma metastasis to the male breast from primary breast carcinoma. This study examined the frequency of PSA, PSAP, and hormone receptor expression in male breast carcinoma (MBC), female breast carcinoma (FBC), and gynecomastia. Methods Immunohistochemical staining for PSA, PSAP, AR, ER, and PR was performed on tissue microarrays representing six cases of gynecomastia, thirty MBC, and fifty-six FBC. Results PSA was positive in two of fifty-six FBC (3.7%), focally positive in one of thirty MBC (3.3%), and negative in the five examined cases of gynecomastia. PSAP expression was absent in MBC, FBC, and gynecomastia. Hormone receptor expression was similar in males and females (AR 74.1% in MBC vs. 67.9% in FBC, p = 0.62; ER 85.2% vs. 68.5%, p = 0.18; and PR 51.9% vs. 48.2%, p = 0.82). Conclusions PSA and PSAP are useful markers to distinguish primary breast carcinoma from prostate carcinoma metastatic to the male breast. Although PSA expression appeared to correlate with hormone receptor expression, the incidence of PSA expression in our population was too low to draw significant conclusions about an association between PSA expression and hormone receptor status in breast lesions.